Dark rites [large type] - Graham, Heather (Graham, Heather. Krewe of hunters, 2017)
A series of bizarre assaults is mystifying Boston police: an unknown attacker is viciously beating random strangers and leaving a note quoting an old warning about witchcraft. History professor Alex Maple was one of the victims, and now he's gone missing. Vickie Preston is certain that someone has taken her friend for malicious purposes. She's having blood-drenched visions that seem to be staining her waking life, and the escalating attacks suggest that a dangerous cult is at work behind the scenes--a cult so powerful that its members would rather die than be apprehended. Vickie is grateful to have Special Agent Griffin Pryce and the FBI's elite Krewe of Hunters on her side. She and Griffin are finding their way in an increasingly passionate relationship, and Griffin is desperately trying to keep her safe and the two of them sane amid the disturbing investigation. The search for Alex will take them deep into the wilderness of Massachusetts on the trail of a serial killer, and it will take everything they have to survive the ancient evil that awakens and threatens not just the man they're striving to save but their very souls.